Surface kinetics analysis by direct area measurement: Laser assisted dehydration of α-FeOOH - Mariana Sendova (AIP Advances, 2019)
A novel method for surface kinetics analysis based solely on quantitative image analysis technique is proposed, and implemented for evaluating the activation energy, 110 (10) meV, of laser assisted dehydration of goethite. Millisecond radiative heat transfer via 785 nm laser beam, allowed us to elucidate a transient surface dehydration below 200 °C. In addition, the proposed method evaluates the laser threshold Irradiance - 1.2(1) μW/μm2 and its temperature dependence. The complementary contributions of radiative (transient) and conductive (equilibrium) heat transfer to the sample provides viable physical elucidation of the observed phenomenon - dehydrated spot surface area, variations with the laser power and the equilibrium temperature. The method allows effectively to isolate and study surface process and can be efficiently applied for any pulse laser assisted surface transformation, when the initial and final products have visual contrast.